Influence of social relations on human mobility and sociality: a study of social ties in a cellular network - Santi Phithakkitnukoon (2018)
© 2016, Springer-Verlag Wien. Personal networks can influence human behavior in many aspects. This article presents a correlation analysis of social tie strength and individual behavior concerning mobility and sociality. The study uses a large-scale mobile phone data (110,213 subjects) from which behavior indicators for both mobility and sociality are inferred and used for the analysis. Mobility diversity, dispersion, and range are considered as mobility behavior indicators. Call frequency, call duration, and degree (number of social ties) are considered for sociality. The results show that people tend to have a more similar behavior with their closer ties for most of considered individual behavior indicators, except for the mobility dispersion.